Beliefs about history, the meaning of historical events and culture of war - Bobowik, Magdalena (2010)
This study examines beliefs concerning the content of history, the meaning of Second World War (WWII) and the evaluation of historical events in relation to pro-war attitudes. Participants were 1183 university students from Spain, Portugal, Argentina, Brazil, Peru and Cape Verde. Four supra-level dimensions in the representations of the past were found: History as progress and leaders-oriented, history as focused on justifying calamities, history as violence and catastrophe, and history as meaningless. The prevalent positive beliefs about history were linked with enthusiasm to fight in a future war for one’s country.